Chemical composition of four different species of the Waltheria genus. (October 2018) - Caridade, Taíza Nayara S.; Araújo, Rusceli D.; Oliveira, Anne Natália A.; Souza, Taiannie Soriano A.; Ferreira, Nara Cristina F.; Avelar, Deusielly S.; Teles, Yanna Carolina F.; Silveira, Edilberto Rocha; Araújo, Renata Mendonça
Abstract: This study aimed the phytochemical investigation of four different species of the genus Waltheria ( W. douradinha, W. ferruginea, W. indica and W. cinerencens), collected in the Northeast of Brazil. Different species of the genus previously studied showed the presence of flavonoids and alkaloids as major constituents, being compatible with this study, that led to the isolation of eight substances, two lupan-type triterpenes: betulonic (3 ) and betulinic acid (4 ), five flavonoids: 5-hydroxy-3, 3′, 4′, 7-tetra-methoxy-flavone (retusine, 1 ), 5-hydroxy-3, 4′, 7-tetramethoxy-flavone (2 ), kaempferol-3-O-β- (6 ″-coumaroyl)-glucopyranoside (tiriloside, 5 ), 3-O-β-glucopyranoside (astragalin, 6 ), quercetin-3-O-α-glucopyranoside (7 ) and quercetin-3-O-β-glucopyranoside (7′ ), and a dibenzamide derivative asperphenamate (8 ), also known as auranamide. There are previous reports of the occurrence of amide structures and lupan-type triterpenes from Malvaceae. In addition to, the compound5 (tiliroside), isolated for the first time from the studied species, is the predominant substance in several Malvaceae species. The obtained results contributed to consolidate the chemotaxonomic knowledge of Waltheria and Malvaceae family.